2014
DOI: 10.1002/ima.22080
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve modulation using focused pulsed ultrasound: Potential applications and preliminary observations in a rat

Abstract: The use of focused ultrasonic waves to modulate neural structures has gained recent interest due to its potential in treating neurological disorders non-invasively. While several papers have focused on the use of ultrasound neuromodulation on peripheral nerves, none of these studies have been performed on the vagus nerve. We present preliminary observations on the effects of focused pulsed ultrasound (FPUS) on the conduction of the left cervical vagus nerve of a Long Evans rat. Ultrasound energy was applied at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 15 publications
4
54
1
Order By: Relevance
“…Investigating neural connectivity-how two connected regions interact by stimulating one area and recording in another-is the most straightforward application. Our approach was to perform the feasibility of such study by studying the interaction within the peripheral nervous system (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating neural connectivity-how two connected regions interact by stimulating one area and recording in another-is the most straightforward application. Our approach was to perform the feasibility of such study by studying the interaction within the peripheral nervous system (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…We, along with some other research groups, have demonstrated that US stimulation on the PNS, with I SPTA between 1 and 200 W/cm 2 , is unlikely to induce a sufficient temperature change in the target region to elicit temperature-driven neuromodulation [43,47]. This intermediate intensity range has been explored on the PNS by several neuromodulation studies, which have been systematically reviewed in the subsequent sections.…”
Section: Intensitymentioning
confidence: 97%
“…Few studies have explored the cellular effects of focused thermal energy due to LIFU, but it is plausible that even small changes in temperature modulate excitability given the temperature dependence of membrane potentials of neurons [87]. Additionally, changes in temperature are known to affect ion channel conductance, enzymatic activity, and equilibrium potentials, resulting in complex dynamical changes of neuron firing rates [88][89][90].…”
Section: Low-intensity Ultrasoundmentioning
confidence: 99%